Diet of the ocelot, Leopardus pardalis (Carnivora: Felidae), in the Neotropical region: a review analysis and new data from central Brazil - Wellington Hannibal; José S.P. de Oliveira; Valquiria V. Figueiredo; Rafael G. Cabral Filho; Lucas de O. Sampaio; Kárita G. de Oliveira; Hermes W.P. Claro (Zoologia (Curitiba), 2025)
ABSTRACT This study reports new data on the diet of the ocelot, Leopardus pardalis, in the Brazilian Cerrado, and reviews the literature data on the diet of the species in the Neotropical region, based on 22 studies. One hundred and twenty-one vertebrate species, in addition to arthropods and plants, are consumed. The highest diversity of prey items, mainly small mammals, was revealed by scat analysis, the most common method used. Analysis of road killed specimens also revealed new dietary records. The wide prey selection, influenced by availability and habitat, enables the ocelot to thrive despite environmental disturbances. This dietary flexibility underscores the importance of diverse sampling methods to fully understand ocelot feeding behavior and habitat needs.